2015
DOI: 10.1017/thg.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Height in Twins: A Cohort and Within-Pair Analyses Study

Abstract: In singletons, asthma may be associated with shorter height and delayed growth during adolescence. Yet, these studies do not account for heritability of asthma, puberty/menarche, and height. We aimed to study the association between asthma and puberty in boys and menarche in girls, and height, in a cohort of twins and subsequently in same-sex twin pairs discordant for asthma. From a Swedish twin cohort, parentand self-reported data on asthma, puberty/menarche, and height were collected. Pubertal staging was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…A total of 22,488 records were retrieved, of which 64 articles (reporting 57 studies) met the criteria to be included in the review. E5 , E10 , E11 , E12 , E13 , E14 , E15 , E16 , E17 , E18 , E19 , E20 , E21 , E22 , E23 , E24 , E25 , E26 , E27 , E28 , E29 , E30 , E31 , E32 , E33 , E34 , E35 , E36 , E37 , E38 , E39 , E40 , E41 , E42 , E43 , E44 , E45 , E46 , E47 , E48 , E49 , E50 , E51 , E52 , E53 , E54 , E55 , E56 , E57 , E58 , E59 , E60 , E61 , E62 , E63 , E64 , E65 , E66 , E67 , E68 , E69 , E70 , E71 , E72 In total, 554,293 participants were analyzed across the included studies. Of the 57 studies, 22 were included in at least ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22,488 records were retrieved, of which 64 articles (reporting 57 studies) met the criteria to be included in the review. E5 , E10 , E11 , E12 , E13 , E14 , E15 , E16 , E17 , E18 , E19 , E20 , E21 , E22 , E23 , E24 , E25 , E26 , E27 , E28 , E29 , E30 , E31 , E32 , E33 , E34 , E35 , E36 , E37 , E38 , E39 , E40 , E41 , E42 , E43 , E44 , E45 , E46 , E47 , E48 , E49 , E50 , E51 , E52 , E53 , E54 , E55 , E56 , E57 , E58 , E59 , E60 , E61 , E62 , E63 , E64 , E65 , E66 , E67 , E68 , E69 , E70 , E71 , E72 In total, 554,293 participants were analyzed across the included studies. Of the 57 studies, 22 were included in at least ...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies exclusively investigated endogenous hormones, 20 exclusively investigated exogenous hormones, and 11 investigated both. Of the 37 studies on endogenous hormones, 9 focused on puberty, E13 , E24 , E28 , E33 , E35 , E53 , E54 , E56 , E67 , E70 22 on menarche, E14 , E21 , E23 , E24 , E25 , E29 , E30 , E31 , E34 , E37 , E38 , E43 , E44 , E45 , E48 , E50 , E53 , E54 , E56 , E57 , E60 , E62 , E63 , E64 , E71 , E72 5 on menstruation, E22 , E25 , E30 , E43 , E44 , E45 , E66 and 11 on menopause. E15 , E17 , E27 , E32 , E36 , E39 , E40 , E42 , E43 , E44 , E45 , E62 , E63 , E64 , E68 , E69 Of the 31 studies on exogenous hormones, 17 focussed on hormonal contraceptives (15 observational E23 , E26 , E29 ,…”
Section: Resultsmentioning
confidence: 99%
“…Because asthma runs strongly in families, genetic determinants can be used to elucidate the inheritable causes of asthma. It is well accepted that asthma is a complex disease with both genetic and environmental factors contributing to its development . Twin studies provided early evidence of genetic influence on the development of asthma .…”
Section: Baseline Characteristics Of the Subjectsmentioning
confidence: 99%
“…The co-twin control model is a type of twin differences model that focuses exclusively on MZ pairs who are discordant either for a disease or for an exposure, such as an environmental factor. This model has recently been used to investigate environmental contributions to the associations between BMI and cardiovascular disease (Song et al, 2015), between height and asthma (Protudjer et al, 2015) and between pain risk factors and low back pain (Oliveira et al, 2015). One notable study with this design demonstrated that smoking was associated with a reduction of 5-10% in bone density, thereby conferring a high risk of fracture (Hopper & Seeman, 1994).…”
Section: Twin Differences Modelsmentioning
confidence: 99%